(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the paper is described new database created for estimating and forecasting of epidemiological and epizootological state in natural origin areas, for example for the Sari-Dzhas sub-region of plague circulation, which is located in the Issyk-Kul region of Kyrgyzstan. The database can be used for different inter-disciplinary research.